Case Report: Surgical Treatment of Type IV Spinal Dermoid Sinus in a Shiba Inu - Takahashi, Kaho; Kimura, Shintaro; Chambers, James K.; Nakano, Yukiko; Ishikawa, Takeshi; Maeda, Sadatoshi; Kamishina, Hiroaki (Frontiers in Veterinary Science, 2022)
A 2-year-old spayed female Shiba Inu was presented with progressive non ambulatory bilateral paraparesis, back pain, and urinary incontinence. CT and MRI revealed multiple vertebral malformations and type IV dermoid sinus. Hemilaminectomy was performed in T1-T5 to remove the dermoid sinus and granulomatous lesion that infiltrated into the spinal cord parenchyma. Histopathological examination of the excised tissue revealed type IV dermoid sinus with granulomatous meningomyelitis. After surgery, back pain was resolved, and the dog recovered ambulation and voluntary urination at the time of follow-up 4 months after surgery.